Faktor yang Berhubungan dengan Kejadian Dismenore Pada Remaja Putri di MTS Negeri 3 Medan Tahun 2019 - Nurul Mouliza (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Dysmenorrhea is a complaint that is often experienced in adolescent girls during menstruation precisely in the lower abdomen. The incidence of dysmenorrhea in Indonesia is 76%. The results of an initial survey of 22 young women had 16 young women experiencing dysmenorrhea and 6 other young women not experiencing dysmenorrhea. The purpose of this study was to determine the factor associated with dysmenorrhea in Teenage girls in MTs State 3 Medan in 2019. Methods this research was conducted with an analytic survey research design with a cross-sectional approach. The population is young women in MTS State 3 Medan, taken by simple random sampling technique amounted to 57 people. Data analysis used univariate analysis using frequency distribution and bivariate analysis using chi-square test. Chi-square test results obtained value of P-Value = .045 which means there is a significant relationship between the age of menarche with dysmenorrhea, P-Value = .033 which means there is a significant relationship between menstrual period with dysmenorrhea, P-Value = .009 which it means that there is a significant relationship between family history and dysmenorrhea in MTs State 3 Medan. Based on the results of research can be concluded that there is an age relationship menarche, long menstruation and family history with Dysmenore in young women in MTs Negeri 3 Medan in 2019.